2018
DOI: 10.1111/eth.12729
|View full text |Cite
|
Sign up to set email alerts
|

Different colour morphs of the poison frog Andinobates bombetes (Dendrobatidae) are similarly effective visual predator deterrents

Abstract: Aposematism is the use of warning signals to advertise unpleasant or dangerous defences to potential predators. As the effectiveness of this strategy depends on predator learning, little variation is expected in aposematic warning signals, as similar signals facilitate predator learning. However, warning signals are frequently variable in aposematic species. Such variability could arise as a result of geographic variation in the interpretation that local predators give warning signals. We tested this divergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…The fitness of aposematic prey increases with density [18,19], meaning that colonization of novel environments (or any area with low population density) could be less likely in aposematic lineages. Field studies have also shown that local colour phenotypes in aposematic species (familiar to predators) suffer lower predation rates compared with novel phenotypes [60][61][62]; although see [31,63,64]. Aposematism could restrict dispersal between populations of the same species that have diverged phenotypically.…”
Section: Discussionmentioning
confidence: 99%
“…The fitness of aposematic prey increases with density [18,19], meaning that colonization of novel environments (or any area with low population density) could be less likely in aposematic lineages. Field studies have also shown that local colour phenotypes in aposematic species (familiar to predators) suffer lower predation rates compared with novel phenotypes [60][61][62]; although see [31,63,64]. Aposematism could restrict dispersal between populations of the same species that have diverged phenotypically.…”
Section: Discussionmentioning
confidence: 99%
“…although see [31,61,62]. Aposematism could restrict dispersal between populations of the same species that have diverged phenotypically.…”
Section: Discussionmentioning
confidence: 99%
“…These prototypes were designed with two postures: a ‘resting’ posture, as frogs are commonly found in nature, and a defensive posture, which includes the elevation of the hind legs, body inflation, and slightly hidden head (Martins, 1989). From the polymer clay prototypes we made the silicon‐rubber moulds which were then filled with paraffin wax to obtain the frog models, following the procedures described in previous studies (Casas‐Cardona et al, 2018; Rojas et al, 2014). The standard size of the models was 3.5 cm ± 0.58, a measure obtained from the average of the SVL of the photographed frogs.…”
Section: Methodsmentioning
confidence: 99%